El diario de Dan Grend: situaciones de un joven dentro del espectro autista - Puentes Sanabria, Dayana Alejandra; Ramírez Padilla , Xiomara Katerine (Lee La LEE, 2023)
El diario de Dan Grend: situaciones de un joven dentro del espectro autista